The digital synaptic neural substrate : a new approach to computational creativity /: a new approach to computational creativity. (2016) - Iqbal, Azlan; Guid, Matej; Colton, Simon, 1973-; Krivec, Jana; Azman, Shazril; Haghighi, Boshra
No abstract available